Human Capital and Economic Growth in Sub Saharan Africa Countries: ARDL and ECM Analysis - Matashu, Martha; Skhephe, Melikhaya (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2022)
The long-run relationship between human capital and economic growth in Sub Saharan African (SSA) countries was examined using An ARDL and ECM cointegration analysis approach. The endogenous and human capital theory posits that human capital accumulated acquired from the education system contributes to economic growth in any economy. Despite many years of huge government expenditure in education, SSA countries appears to experience little or no economic growth. Studies on the long term effects of human capital on economic growth in SSA countries remain few despite a growing body of research in literature. Using data from 37 SSA countries for the year 2000- 2018 an Autoregressive Distributed Lag ARDL and Error Correction Model (ECM) cointegration the study estimated a Dynamic Fixed Effects model (DFE) to examine the long run relationship between human capital and economic growth. The findings revealed that a cointegration relationship exist between human capital and economic growth. Secondary education had a significant but weak positive effect on economic growth in the short run and a weak negative effect on economic growth in the long run. Primary education however, had an insignificant contribution to economic growth both in the short and long run. Physical capital hadsignificant and strong positive effect on economic growth in the short run whilst in the long run it has an insignificant effect. SSA countries interested in enhancing long run term economic growth through human capital should consider promoting access to secondary school enrolment and improving the quality of primary education. The study providedempirical evidence on the short and long run contribution of human capital to economic growth in SSA countries.